Vitamin D receptor polymorphisms and vitamin D insufficiency are not associated with sepsis in critically ill children: a case-control study - Iman Shaheen; Rasha Afifi; Nelly Abulata; Reham Aboukhalil; Basant Meligy; HebatAllah F. Algebaly; Omnia Y. Abd El Dayem (SpringerOpen, 2022)
Highlights • Vitamin D level was low in both pediatric septic ICU patients and age- and sex-matched healthy controls. • Vitamin D levels were unaffected by VDR polymorphisms, and their distribution was similar in both groups. • Neither the need for mechanical ventilation or inotropic treatment nor the sepsis outcome was impacted by vitamin D or VDR polymorphisms.